A flexible framework for data exchange and presentation between wireless sensor networks and personal devices - Miguelez Garcia, Ruben (2007)
This paper presents the framework of an interface between wireless sensor networks and personal devices like PDAs, cellular phones and laptops. It possesses a flexible architecture that can be adapted easily to display any kind of data received from the network sensors using content description. The most relevant properties of this system are: portability (it can be used on any device with a standard browser), expandability (it can act as a gateway for higher systems), adaptability (the information can be presented in many different ways) and scalability (several sensor networks can be controlled at the same time). This system is currently being used display information retrieved from a Bluetooth based wireless sensor network platform which operates onboard of an unmanned aerial vehicle (UAV).